Adolphe Appia Prophet of the Modern Theatre, A Profile (Wesleyan University Press, 1968)
In the complex art of theatrical design and production, the first decades of this century saw no more original or lastingly influential innovator than Adolphe Appia (1862-1928). Partly through his startling stage designs, more perhaps through his published writings and personal contacts with men of the theatre throughout Europe, his ideas and theories wrought a revolution whose effects are everywhere today. Yet the details of his work and the extent of his influence have heretofore had no proper recognition or even complete recording. Concentrating on Appia's aesthetic ideas, writings, and professional accomplishments, this book traces his career from early days as a music student in his native Geneva, Paris, and Germany through his association with Houston Stewart Chamberlain and the Bayreuth circle, his exchanges with Gordon Craig, his work with Jaques-Dalcroze at Hellerau, and his crowning production (for Toscanini) of Tristan at La Scala, to his declining years and death in 1928. The arrangement is topical rather than chronological. Throughout, the growth of Appia's theories and the steps in his career are shown in relation to the cultural milieu, especially the theatre, of his place and time. His personality and character too become evident: and thus one comes to know a man of genius who, though reserved with strangers, commanded the devoted respect of those who worked with him most closely.